2017
DOI: 10.1016/j.micpath.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of non-aflatoxigenic strains of Aspergillus flavus as potential biocontrol agent for the management of aflatoxin contamination in groundnut

Abstract: In the present study, nine non-aflatoxigenic Aspergillus flavus strains were evaluated for their potential to reduce A. flavus infection and aflatoxin contamination in groundnut. Genetic characterization of these strains revealed six different deletion patterns (A-F) for thirteen examined genes from the aflatoxin biosynthesis pathway. Strain AFGS5 recorded maximum number of gene deletion (F) which included 12 out of 13 tested genes. Our findings indicated that aflR was the most frequently absent gene among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Research programs at UC Davis and collaborating universities in Argentina and Spain have identified through laboratory tests, atoxigenic A. flavus isolates with potential as biocontrol agents for use on those nations, but the efficacy of those isolates has not been tested under field conditions [68][69][70]. Similarly, studies for identifying potential A. flavus biocontrol isolates are being conducted in other countries including, China [71], India [72], Thailand [73,74], and Serbia [75].…”
Section: From Single To Multiple Isolatesmentioning
confidence: 99%
“…Research programs at UC Davis and collaborating universities in Argentina and Spain have identified through laboratory tests, atoxigenic A. flavus isolates with potential as biocontrol agents for use on those nations, but the efficacy of those isolates has not been tested under field conditions [68][69][70]. Similarly, studies for identifying potential A. flavus biocontrol isolates are being conducted in other countries including, China [71], India [72], Thailand [73,74], and Serbia [75].…”
Section: From Single To Multiple Isolatesmentioning
confidence: 99%
“…However, as Ehrlich [111] reviewed, there were a lot of challenges to using nontoxigenic Aspergillus species. Primarily, due in part to inherent diversity of Aspergillus species and genetic complexity, genetic mutations may happen in nontoxigenic Aspergillus spp., which potentially leads atoxigenic strains to mutate to aflatoxigenic strains; therefore, from a long-term security, nontoxigenic Aspergillus strains were also suggested to be cautiously used [112][113][114].…”
Section: Inhibitory Mechanisms By Nontoxigenic Aspergillus Sppmentioning
confidence: 99%
“…However, competition of other mycotoxigenic pathogens such as F. pseudograminearum through nutrient competition [50] and F. culmorum and F. graminearum [51] were also reported. It has been demonstrated that atoxigenic A. flavus strains are powerful BCAs to control the toxigenic strains of A. flavus in cottonseed [52][53][54], maize [27,[55][56][57] and various types of nuts [58][59][60][61]. Currently, different strains of atoxigenic A. flavus are being used depending on the endemic area and sometimes a mixture of strains is used in the field.…”
Section: Competition For Niche and Nutritionmentioning
confidence: 99%
“…Doster et al used A. flavus strain AF36 as a BCA to control AFs in pistachio orchards for four consecutive seasons (2008-2011) and he could diminish AFs level by 20-45% [114]. In groundnuts, more trials in vitro [61,66] and in the field [58][59][60] have been done. Zhou et al 2015 found a positive correlation between AFs reduction rate and inoculum dose while Hulikunte Mallikarjunaiah et al 2017 measured total AFs in rhizospheric and geocarpospheric soil and groundnut seeds after he treated them with two strains isolated from India.…”
Section: Aflatoxinsmentioning
confidence: 99%
See 1 more Smart Citation